INOVASI CUSTOMER FOCUSED MELALUI COMMAND CENTER UNTUK PENINGKATAN EFEKTIVITAS PENANGANAN LAPORAN PELANGGAN DI PT PLN (PERSERO) UP3 BANGKA - Warassih, Anggit Praharasty; Supriyoso, Patria (Jurnal Manajemen dan Profesional, 2024)
In the electricity industry, the products produced will always coexist with the services provided. Various service patterns, strategies and innovations will continue to be developed. PT PLN (Persero) is a company that provides electricity with a lifetime guarantee. When a customer's electricity supply stops, the customer will try to find a communication channel to inform them of the electricity disruption they are experiencing in the hope that it can be restored as soon as possible. However, handling customer reports is considered ineffective because it involves a lot of staging and is still manual. The Bangka Command Center was formed to carry out the task of serving disturbance reports throughout the PT PLN (Persero) UP3 Bangka work area spread across five Customer Service Units (ULP). Bangka Command Center is a form of Customer Focused innovation created to increase the effectiveness of handling customer reports and is expected to meet customer expectations for excellent service from year to year